Extended pelvic lymphadenectomy and various radical prostatectomy techniques: is pelvic drainage necessary?. (29th January 2013) - Danuser, Hansjoerg; Di Pierro, Giovanni Battista; Stucki, Patrick; Mattei, Agostino
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The occurence of lymphoceles in patients after radical prostatectomy is well known (2–10%). It appears that patients undergoing open extraperitoneal radical prostatectomy develop more lymphoceles than patients undergoing robot‐assisted radical prostatectomy with transperitoneal access. The present study investigates in a prospective randomized manner whether the time of drainage (1 vs 7 days) makes a difference or whether drainage is even necessary. The study data, collected in the same institution, are compared with the incidence of lymphocele in patients treated by robot‐assisted radical prostatectomy. Objective To investigate whether routine drainage is advisable after open extended pelvic lymph node dissection (ePLND) and retropubic radical prostatectomy (RRP) by measuring the incidence of lymphoceles and comparing these results with those of a series of robot‐assisted radical prostatectomy (RARP) and ePLND. Patients and Methods A total of 331 consecutive patients underwent ePLND and RRP or RARP. The first 132 patients underwent open ePLND and RRP and received two pelvic drains; these patients were prospectively randomized into two groups: group 1 (n = 66), in which the drains were shortened on postoperative (PO) days 3 and 5 and removed on PO day 7, and group 2 (n = 66), in which the drains were removed on PO day 1. The next 199 patients were assigned to two consecutive groups not receiving drainage: group 3 (n = 73) undergoing open ePLND and RRP, followed by group 4 (n = 126) treated by transperitoneal robot‐assisted ePLND and RARP. All patients had ultrasonographic controls 5 and 10 days and 3 and 12 months after surgery. Results Lymphoceles were detected in 6.6% of all patients, 3.3% of whom were asymptomatic and 3.3% of whom were symptomatic. Symptomatic lymphoceles were detected in 0% of group 1, 8% of group 2, 7% of group 3 and 1% of group 4, with groups 2 and 3 differing significantly from group 4 (P < 0.05). In total, 5% of all patients undergoing open RRP (groups 1–3) had symptomatic lymphoceles vs 1% of patients undergoing RARP (group 4) (P = 0.06). Nodal‐positive patients had significantly more symptomatic lymphoceles than nodal‐negative patients (10% vs 2%) (P < 0.02). Conclusions Symptomatic lymphoceles occur less frequently after open RRP and pelvic drainage over 7 days than after open RRP and pelvic drainage over 1 day or without drainage. Patients undergoing RARP without drainage had significantly fewer lymphoceles than patients receiving open RRP without drainage.